2017
DOI: 10.31989/ffhd.v7i10.377
|View full text |Cite
|
Sign up to set email alerts
|

The modified amino sugar N-Butyryl Glucosamine fed to ovariectomized rats preserves bone mineral through increased early mineralization, but does not affect body composition

Abstract: Citation: Anastassiades T., Ress-Milton K., Hopman W.M., The modified amino sugar NButyryl Glucosamine fed to ovariectomized rats preserves bone mineral through increased early mineralization, but does not affect body composition. Functional Foods in Health and Disease 2017; 7(10): 795-815 ABSTRACT Background: The toxicities of pharmaceuticals for chronic arthritis and osteoporosis should be of concern to consumers. This partially accounts for the popularity of consumption of the amino sugar glucosamine, in-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…At KEGG level 3, correlation analysis revealed that there is a negative correlation between amino sugar and nucleotide sugar metabolism and decreased Firmicutes (P < 0.05) (Table 3), and this rising trend of amino sugar and nucleotide sugar metabolism may disturb the normal acetylation of amino sugars by glycosyltransferases and affect the component of glycoproteins, proteoglycans, glycolipids, and long-chain polymers (Anastassiades et al 2017). Increased Bacteroidetes was negatively related to ABC transporters and aminoacyl-tRNA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…At KEGG level 3, correlation analysis revealed that there is a negative correlation between amino sugar and nucleotide sugar metabolism and decreased Firmicutes (P < 0.05) (Table 3), and this rising trend of amino sugar and nucleotide sugar metabolism may disturb the normal acetylation of amino sugars by glycosyltransferases and affect the component of glycoproteins, proteoglycans, glycolipids, and long-chain polymers (Anastassiades et al 2017). Increased Bacteroidetes was negatively related to ABC transporters and aminoacyl-tRNA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%